Chemistry, a humanistic approach - Vallarino, L. M.; Quagliano, James V. (James Vincent), 1915- (New York : Webster Division, McGraw-Hill, 1975)
Examines the basic concepts of chemistry with emphasis on the role of chemistry and chemical technology in modern society.
Includes index.
Keywords: Chemistry; Chemistry